Laboratory Evaluation of Primary Immunodeficiencies from Secondary Immunodeficiencies in the Context of Hematological Malignancies: Review - Albuthely, Fayz Eid; Alsaid , Abdulrahman Mulla; Aljohani , Bakr Mohammed Hamoud; Alsulaimani , Raid Ghazi; Aljohani , Khalid Marzooq; Almrwani, Naif Snead; Alhebaishi, Ali Eid; Shahata, Moayed Anwar; Alharbi, Hamed Abdullah Khalf; Alrefai , Ghazi Ateyatullah; Aljohani, Naji Omear Mansour (Journal of Ecohumanism, 2024)
Background: Primary immunodeficiencies (PIDs) represent a diverse group of congenital disorders characterized by defects in the immune system. Distinguishing PIDs from secondary immunodeficiencies (SIDs) is critical, particularly in patients with hematological malignancies, as misdiagnosis can lead to inadequate treatment and poor patient outcomes. Methods: This review synthesizes case studies and recent literature to explore the clinical overlap between PIDs, SIDs, and hematological malignancies. A comprehensive search of national databases and clinical guidelines was conducted to analyze patterns in diagnosis, treatment strategies, and the implications of immunodeficiency in cancer prognosis. Results: Findings indicate that a significant proportion of patients with hematological malignancies also exhibit signs of immunodeficiency, complicating diagnosis. Case studies highlight instances where SIDs obscure underlying PIDs, particularly in patients treated with immunosuppressive therapies such as rituximab. The review underscores the importance of early immunological evaluation in patients with recurrent infections and malignancies. Conclusion: The differentiation between PIDs and SIDs is paramount for optimizing patient management and therapeutic interventions. Enhanced awareness and interdisciplinary approaches are essential in the timely identification of PIDs, particularly in patients presenting with hematological malignancies. Future research should focus on developing standardized screening protocols for immunodeficiencies in oncology settings to improve patient outcomes